2022
DOI: 10.7759/cureus.29341
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Hernia Repair Using Ventralex® ST Patch: A Single-Center Study of Clinical Outcomes and Complications

Abstract: BackgroundVentralex® ST (Bard Davol Inc, Warwick, RI) patch is a composite self-expanding and non-absorbable mesh used to reinforce ventral hernia repair. This study was conducted to assess the efficacy, post-operative clinical outcomes, the duration of operation, and complications deciding the post-operative duration/need of hospitalization in patients of small ventral hernia after their open surgical repair using Ventralex ST hernia patch. Materials and methodsWe included 36 patients diagnosed with a small (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are also case reports about mesh migration to bowel after Venralex™ hernia patch used in incisional hernia repair [ 9 ]. Several studies have shown low complication, recurrence and reoperation rates after ventral patch repair for small umbilical hernias [ 5 , 6 , 10 12 ]. Nevertheless, authorities from hernia surgical associations have taken a sceptical view of ventral patches, mainly because of costs and complications and recurrences seen after patch repair has been used in improper situations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also case reports about mesh migration to bowel after Venralex™ hernia patch used in incisional hernia repair [ 9 ]. Several studies have shown low complication, recurrence and reoperation rates after ventral patch repair for small umbilical hernias [ 5 , 6 , 10 12 ]. Nevertheless, authorities from hernia surgical associations have taken a sceptical view of ventral patches, mainly because of costs and complications and recurrences seen after patch repair has been used in improper situations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%